Virtual environment of water molecules for learning and teaching science - Trindade, Jorge (1999)
Virtual reality is an emerging computer visualization technology which allows educators to place their students in to instructional environments heretofore difficult or impossible to achieve. In order to take full advantage of this technology, a virtual environment, "Virtual Water", is being developed. Virtual reality has been recently employed in a few educational applications, but the project presented here is the first application we know of combining aspects as atomic and molecular orbits, electron densities, water molecular dynamics for the liquid and gaseous phases and phase transitions.